Development of breakthrough bleeding model of combined‐oral contraceptives utilizing model‐based meta‐analysis - Huili Chen; Dain Chun; Karthik Lingineni; Serge Guzy; Rodrigo Cristofoletti; Joachim Hoechel; Tianze Jiao; Brian Cicali; Valvanera Vozmediano; Stephan Schmidt (Wiley, 2024)
Abstract Breakthrough bleeding (BTB) is a common side effect of hormonal contraception and is thought to impact adherence to combined oral contraceptives (COCs) but respective dose-response relationships are not yet fully understood. Therefore, the objective of this model‐based meta‐analysis (MBMA) was to establish dose-response for COCs containing different progestin/EE combinations using BTB as the pharmacodynamic endpoint. Data from 25 studies containing BTB information of 4 progestins (desogestrel, drospirenone, gestodene, and levonorgestrel) in combination with ethinyl estradiol (EE) at various dose levels was used for this analysis. The results of our MBMA show that BTB is significantly increased upon initiation of COC use but subsides over time. The time needed for BTB to return to baseline depends on the EE dose and differs marginally between progestins during the initial months of use at the same EE dose. BTB typically returns to baseline within 3 months at the highest (30 μg) dose, whereas it can take significantly longer to reestablish a regular bleeding pattern at lower EE doses (15 and 20 μg), irrespective of the progestin used. The dose-response relationships established for BTB across different progestin/EE combinations can now be used to support the selection of optimal COC dosing/treatment regimens and serve as the scientific basis for evaluating the impact of clinically relevant factors, including drug-drug interactions and demographics, on BTB.